Types Of Synonyms and Their Role in Writing and Speaking Skills - Gapparova Mehribon Tulqin qizi (Zien Journals, 2023)
In this article diverse types of synonyms will be explained and the role of them in writing and speaking will be discussed with relevant examples.
Keywords: definition of synonym; types of synonyms; synonyms which can be any part of the speech